Analisis Kekuatan Purwarupa Swing Arm Untuk Sepeda Motor Listrik: Studi Kasus Pada PT “SC” - Bachri, Karel Octavianus; Soewono, Arka Dwinanda; Nabil, Alfi (Department of Mechanical Engineering Atma Jaya Catholic University of Indonesia, 2023)
In recent years, the automotive industry has been experiencing a significant transition from internal combustion engines that use fossil fuels to electric vehicles. PT “SC” is one of the leading companies engaged in converting and developing electric vehicles in Indonesia. This research aims to conduct a strength analysis of the swing arm prototype developed by PT “SC”. Simulations were performed using SolidWorks software to determine the impact of static loading on the von Mises stress and strain experienced by the swing arm made from SS 400 material. The total load on the swing arm was 1610N based on the electric dynamo's weight and the possible passengers' weight on the electric motorbike. The stress analysis results show that the maximum and minimum Mises stresses ​​are 5.38 x 106 N/m2 and 1.99 x 10-1 N/m2, respectively. This stress produces a maximum displacement value of 4.54 x 10-3 mm. Calculation results from Solidworks found that the safety factor for the swing arm prototype was 43, meaning the design is safe to use.